2015
DOI: 10.1111/gcb.12858
|View full text |Cite
|
Sign up to set email alerts
|

Plant stomatal closure improves aphid feeding under elevated CO2

Abstract: Stomata help plants regulate CO absorption and water vapor release in response to various environmental changes, and plants decrease their stomatal apertures and enhance their water status under elevated CO . Although the bottom-up effect of elevated CO on insect performance has been extensively studied, few reports have considered how insect fitness is altered by elevated CO -induced changes in host plant water status. We tested the hypothesis that aphids induce stomatal closure and increase host water potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 43 publications
0
50
1
2
Order By: Relevance
“…Moreover, a study of Sun et al . () on Acyrthosiphon pisum feeding on Medicago truncatula indicated that elevated CO 2 reduced the stomatal aperture of plants. This induced an increase of phloem and xylem sap ingestion by A. pisum as a result of the decrease in transpiration and the increase in water potential of M. truncatula .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study of Sun et al . () on Acyrthosiphon pisum feeding on Medicago truncatula indicated that elevated CO 2 reduced the stomatal aperture of plants. This induced an increase of phloem and xylem sap ingestion by A. pisum as a result of the decrease in transpiration and the increase in water potential of M. truncatula .…”
Section: Discussionmentioning
confidence: 99%
“…acid signaling, which decreases the stomatal aperture and leaf transpiration, thereby maintaining the leaf water potential that aphids need for feeding (Sun et al, 2015). Arabidopsis mutants that are defective in abscisic acid signaling are more resistant to aphids (Kerchev et al, 2013;Hillwig et al, 2015), which also indicates a more direct role in plant-aphid interactions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ABA can suppress SA-dependent defenses (De Torres Zabala et al, 2009; Jiang et al, 2010; Cao et al, 2011). Concerning aphids, there are several reports that infestation induced ABA levels or ABA-regulated gene expression in Glycine max , M. truncatula , and A. thaliana (Studham and Macintosh, 2013; Guo et al, 2015; Sun et al, 2015; Hillwig et al, 2016). In contrast, another study showed that ABA levels in M. truncatula were not affected or even reduced by A. pisum feeding (Stewart et al, 2016) a pattern we also found in our study, where ABA levels in aphid-infested plants were generally lower or very similar than those in control plants.…”
Section: Discussionmentioning
confidence: 99%